PERAN KEPALA SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN SEKOLAH DI MADARASAH ALIYAH NURUL ISLAM KECAMATAN PULAU PANGGUNG KABUPATEN TANGGAMUS - Irawan, Muhamad Hendri; Januarius, Tetra Jumif (JMPA (Jurnal Manajemen Pendidikan Al-Multazam), 2021)
This study aims to describe the role of the principal: (1) as a leader in improving the quality of education; (2) supporting factors; (3) inhibiting factors and solutions in improving the quality of education. The method used in this research is a qualitative approach with the type of case study research. Data collection techniques in this study were interviews, observation, and documentation. The results obtained from this study are: (1) the role of the principal as a leader in improving the quality of education is to monitor, mediate between teachers and students, discipline, motivate, innovate, liaise with external parties, guide students on an ongoing basis, foster and improve abilities. teachers, and make decisions; (2) supporting factors in improving the quality of education are the number of relationships, foundation support, students are free to choose, facilitate teachers; while the inhibiting factors and solutions are the clash of the system with the service, continuing to follow the service but adjusted to the school's vision and mission; frequent change of teachers, offer through a statement whether or not to continue and provide sufficient salary; certification policy, facilitating the second year by paying attention to student rights; lack of awareness of school residents, providing understanding, assignments, and motivating; the difficulty of implementing digital learning, including certified training and fulfilling infrastructure; the team coordinator is not always at school, communicating and diverting to members; calculate finances manually, using a weekly, quarterly, semester, yearly reporting system; and sometimes due to cost constraints, the program is postponed/takes the lowest nominal.